Ferritic stainless steel and steel sheet

By optimizing the composition of ferritic stainless steel with specific element limits and additions, the challenges of high thermal expansion, reduced conductivity, and compromised workability in SOFC and SOEC separators are addressed, resulting in a material with improved performance for these applications.

JP2025091317APending Publication Date: 2025-06-18DAIDO STEEL CO LTD

Patent Information

Application Number
JP2023206522
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-12-06
Publication Date
2025-06-18

AI Technical Summary

Technical Problem

Ferritic stainless steels used as separators in solid oxide fuel cells (SOFC) and solid oxide electrolysis cells (SOEC) face challenges such as high coefficient of thermal expansion, reduced electronic conductivity due to insulating oxide film formation, and compromised hot workability.

Method used

A ferritic stainless steel composition is optimized with specific limits for elements like C, Si, Mn, P, S, Cu, Ni, Cr, Co, Al, Ti, N, and La, along with optional additions of V, Nb, Ta, and B, to achieve a balance of low thermal expansion, improved oxidation resistance, and maintained hot workability.

Benefits of technology

The optimized ferritic stainless steel exhibits reduced coefficient of thermal expansion, enhanced oxidation resistance, and preserved hot workability, making it suitable for high-temperature applications in SOFC and SOEC separators.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025091317000001_ABST
    Figure 2025091317000001_ABST
Patent Text Reader

Abstract

To provide a ferritic stainless steel and a steel sheet thereof, having excellent oxidation resistance and hot workability.SOLUTION: A ferritic stainless steel contains 0<C≤0.03 mass%, Si≤0.05 mass%, 0.30≤Mn≤1.00 mass%, P≤0.05 mass%, S≤0.05 mass%, Cu≤0.10 mass%, Ni≤0.20 mass%, 20.0≤Cr≤25.0 mass%, Co≤0.10 mass%, Al≤0.10 mass%, 0.01≤Ti≤0.30 mass%, 0<N≤0.03 mass%, and 0.05≤La≤0.30 mass%. The balance is Fe and unavoidable impurities. The ferritic stainless steel further contains at least one selected from the group consisting of 0.05≤V≤2.00 mass%, 0.05≤Nb≤2.00 mass%, 0.05≤Ta≤0.30 mass%, and 0.0010≤B≤0.0100 mass%. A steel sheet is made of the ferritic stainless steel.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to ferritic stainless steel and steel sheets, and more particularly to ferritic stainless steel suitable as a separator for a solid oxide fuel cell (SOFC) or a solid oxide electrolysis cell (SOEC), and a steel sheet using the same.

Background Art

[0002] Ferritic stainless steel is stainless steel having a ferritic structure at normal temperature. Ferritic stainless steel is excellent in heat resistance, oxidation resistance, and cold workability, and has a feature that its coefficient of thermal expansion is smaller than that of other materials. Therefore, the use of ferritic stainless steel as a separator for a solid oxide fuel cell (SOFC) or a solid oxide electrolysis cell (SOEC) has been studied.

[0003] For example, Patent Document 1 discloses a ferritic stainless steel containing a predetermined amount of Cr, C, Si, Mn, P, S, Al, N, Nb, Ni, Mo, Sn, and B, with the balance being Fe and inevitable impurities. The same document describes (A) In order to obtain good oxidation resistance, it is necessary to make the Al content 1.00 mass% or more, but when the Al content exceeds 3.00 mass%, the toughness of the steel decreases. (B) In order to improve the oxidation resistance in a reforming environment, it is necessary to make the Si content 0.50 mass% or more. (C) Such ferritic stainless steel has high oxidation resistance and high high-temperature strength, and is therefore suitable as a high-temperature member for SOFC. is described.

[0004] Patent Document 2 discloses a stainless steel sheet for a separator of a fuel cell containing a predetermined amount of C, Si, Mn, P, S, Cr, Ni, Ti, Al, and N, with the balance being Fe and inevitable impurities. The same document describes (A) When an anodic oxidation treatment is performed on a stainless steel sheet containing a predetermined amount of Cr and Ti, fine precipitates containing Cr and Ti can be precipitated on the surface of the steel sheet, and the contact resistance of the steel sheet can be reduced. Also, (B) Although REM is an element effective for deoxidation, when the REM content exceeds 0.100 mass%, the hot workability deteriorates. is described.

[0005] Patent Document 3 discloses a ferritic stainless steel containing a predetermined amount of Cr, C, Si, Mn, Al, P, S, and N, with the balance being Fe and unavoidable impurities. In the same document, (A) In an Al-containing ferritic stainless steel cold-rolled annealed sheet, when the microstructure is optimized, the creep properties are improved. Also, (B) When the Al content is less than 0.5%, it becomes difficult to form an Al-based oxide film, and thus the effect of suppressing Cr evaporation cannot be obtained. is described.

[0006] Patent Document 4 discloses a steel for a solid oxide fuel cell separator containing a predetermined amount of C, Si, Mn, Ni, Cr, Cu, and Al, further containing one or more of Y, REM, and Zr, with the balance being Fe and unavoidable impurities. In the same document, (A) Si has an effect of improving the oxidation resistance of the separator, and the preferable lower limit of the Si content is 0.05 mass%. Also, (B) In order to improve the oxidation resistance of the separator, it is necessary to add a Cu content of 0.3 mass% or more. Also, (C) When a small amount of Y, REM, or Zr is added, the oxidation resistance and the electrical conductivity of the oxide film can be significantly improved. is described.

[0007] The SOFC includes a single cell in which an anode (fuel electrode) and a cathode (air electrode) are joined to both sides of an electrolyte, and separators disposed on both sides of the single cell. The SOEC has the same structure as the SOFC, but causes a reaction opposite to that of the SOFC. Also, the operating temperature of the SOFC and SOEC reaches several hundred °C. Therefore, the separators are required to have properties such as oxidation resistance, electronic conductivity, and a low coefficient of thermal expansion. Also, in order to reduce the cost of the separators, the materials for the separators are required to have easy processability.

[0008] Regarding this point, the ferrite stainless steel described in Patent Documents 1 and 3 has a large coefficient of thermal expansion because the amount of Al is excessive. Also, when used in a high-temperature oxidation atmosphere, an Al-based oxide is formed on the surface, and the electronic conductivity is likely to decrease. Also, the steel for separators described in Patent Document 4 may prevent the formation of a dense Mn-based oxide (oxide having Cr volatility resistance) in the outermost layer of the separator because the amount of Si is excessive.

[0009] Also, Patent Documents 2 and 4 describe that the addition of REM (so-called "misch metal") is effective in improving oxidation resistance, but Ce contained in REM has a great effect of reducing the hot workability of stainless steel. Also, if excessive N is contained in the stainless steel, REM may combine with N to form precipitates, and the effects of adding REM (for example, improvement of oxidation resistance) may be lost. Furthermore, in Patent Document 4, the upper limit of the amount of C is 0.2 mass%, but the limitation of the addition amount is loose, and the possibility of sensitization is considered.

Prior Art Documents

Patent Documents

[0010]

Patent Document 1

Patent Document 2

Patent Document 3

Patent Document 4

Summary of the Invention

Problems to be Solved by the Invention

[0011] The problem to be solved by the present invention is to provide a ferritic stainless steel having a relatively low coefficient of thermal expansion and excellent in electrical conductivity, oxidation resistance, and hot workability, and a steel sheet using the same.

Means for Solving the Problems

[0012] In order to solve the above problems, the ferritic stainless steel according to the present invention is 0 < C ≤ 0.03 mass%, Si ≤ 0.05 mass%, 0.30 ≤ Mn ≤ 1.00 mass%, P ≤ 0.05 mass%, S ≤ 0.05 mass%, Cu ≤ 0.10 mass%, Ni ≤ 0.20 mass%, 20.0 ≤ Cr ≤ 25.0 mass%, Co ≤ 0.10 mass%, Al ≤ 0.10 mass%, 0.01 ≤ Ti ≤ 0.30 mass%, 0 < N ≤ 0.03 mass%, and 0.05 ≤ La ≤ 0.30 mass% and the balance consists of Fe and inevitable impurities, 0.05 ≤ V ≤ 2.00 mass%, 0.05 ≤ Nb ≤ 2.00 mass%, 0.05 ≤ Ta ≤ 0.30 mass%, and 0.0010 ≤ B ≤ 0.0100 mass% and further contains at least one element selected from the group consisting of.

[0013] The steel sheet according to the present invention is made of the ferritic stainless steel according to the present invention. [Effects of the Invention]

[0014] Ce contained in REM (misch metal) has the effect of improving the oxidation resistance of ferritic stainless steel, but has a great effect of reducing the hot workability. On the other hand, La has the effect of improving the oxidation resistance of ferritic stainless steel and has a smaller effect of reducing the hot workability compared to Ce. Therefore, when an appropriate amount of La is added to ferritic stainless steel instead of Ce, the oxidation resistance can be improved without significantly reducing the hot workability of ferritic stainless steel.

[0015] In ferritic stainless steel, when the Al content is limited, an increase in the coefficient of thermal expansion and a decrease in electron conductivity due to the formation of an insulating oxide film can be suppressed. In addition, Mn and Ti have the effect of forming Cr-Mn spinel-type oxides or Ti oxides when ferritic stainless steel is exposed to a high-temperature oxidation atmosphere, and suppressing the volatilization of CrO3. Furthermore, Ti, as well as V, Nb, Ta, and B all have the effect of suppressing the formation of Cr carbides and Cr nitrides. Therefore, when one or more of the elements V, Nb, Ta, and B are further added in addition to Ti, the oxidation resistance of ferritic stainless steel is further improved. [Brief Description of the Drawings]

[0016]

Figure 1

[0017] Hereinafter, an embodiment of the present invention will be described in detail. [1. Ferritic Stainless Steel] [1.1. Main Components] The ferritic stainless steel according to the present invention contains the following elements, and the balance consists of Ni and inevitable impurities. The types of additive elements, their component ranges, and the reasons for their limitations are as follows.

[0018] (1) 0 < C ≤ 0.03 mass%: When the C content becomes excessive, Cr carbides are formed, which may reduce the Cr concentration in the matrix phase and lower the oxidation resistance of the steel. Therefore, the C content needs to be 0.03 mass% or less. The C content is preferably 0.02 mass% or less, or 0.01 mass% or less. On the other hand, C is also an element that inevitably mixes in, and excessive reduction will lead to higher costs. Therefore, it is preferable to select an optimal value for the C content in consideration of the manufacturing cost.

[0019] (2) Si ≤ 0.05 mass%: When the Si content becomes excessive, Si-based oxides may be formed on the outermost surface of the steel during oxidation, which may increase the contact resistance of the steel. Therefore, the Si content needs to be 0.05 mass% or less. The Si content is preferably 0.03 mass% or less. On the other hand, Si is also an element that inevitably mixes in, and excessive reduction will lead to higher costs. Therefore, it is preferable to select an optimal value for the Si content in consideration of the manufacturing cost.

[0020] (3) 0.30 ≤ Mn ≤ 1.00 mass%: When a ferritic stainless steel containing a large amount of Cr is heated to a high temperature, CrO3 is likely to volatilize from the ferritic stainless steel. The air electrode (cathode) of the SOFC is easily poisoned by the volatilized Cr. In contrast, Mn has the effect of forming an oxide (Mn-based spinel oxide) together with Cr during oxidation and suppressing the volatilization of CrO3. To obtain such an effect, the Mn content needs to be 0.30 mass% or more. The Mn content is preferably 0.40 mass% or more. On the one hand, since Mn itself is prone to oxidation, when the amount of Mn becomes excessive, the oxidation resistance of the steel may decrease. Therefore, the amount of Mn needs to be 1.00 mass% or less. The amount of Mn is preferably 0.80 mass% or less.

[0021] (4) P ≤ 0.05 mass%: When the amount of P becomes excessive, the hot workability and cold workability may decrease. Therefore, the amount of P needs to be 0.05 mass% or less. The amount of P is preferably 0.03 mass% or less. On the other hand, P is also an element that inevitably mixes in, and excessive reduction will lead to higher costs. Therefore, it is preferable to select an optimal value for the amount of P in consideration of the manufacturing cost.

[0022] (5) S ≤ 0.05 mass%: When the amount of S becomes excessive, the hot workability and cold workability may decrease. Therefore, the amount of S needs to be 0.05 mass% or less. The amount of S is preferably 0.03 mass% or less. On the other hand, S is also an element that inevitably mixes in, and excessive reduction will lead to higher costs. Therefore, it is preferable to select an optimal value for the amount of S in consideration of the manufacturing cost.

[0023] (6) Cu ≤ 0.10 mass%: When the amount of Cu becomes excessive, the hot workability and cold workability may decrease. Therefore, the amount of Cu needs to be 0.10 mass% or less. The amount of Cu is preferably 0.05 mass% or less. On the other hand, excessive reduction of the amount of Cu may lead to higher costs. Therefore, it is preferable to select an optimal value for the amount of Cu in consideration of the manufacturing cost.

[0024] (7) Ni ≤ 0.20 mass%: When the amount of Ni becomes excessive, the thermal expansion coefficient of the steel may increase. Therefore, the amount of Ni needs to be 0.20 mass% or less. The amount of Ni is preferably 0.10 mass% or less. On the other hand, excessive reduction of the Ni content may lead to an increase in cost. Therefore, it is preferable to select an optimal value for the Ni content in consideration of the manufacturing cost.

[0025] (8) 20.0 ≦ Cr ≦ 25.0 mass%: Cr has the effect of improving the oxidation resistance of steel. In order to obtain such an effect, the Cr content needs to be 20.0 mass% or more. The Cr content is preferably 21.0 mass% or more, or 21.5 mass% or more. On the other hand, when the Cr content becomes excessive, a large amount of CrO3 is generated when the steel is heated in a high-temperature oxidation atmosphere, and CrO3 is likely to volatilize from the surface of the steel. Therefore, the Cr content needs to be 25.0 mass% or less. The Cr content is preferably 24.0 mass% or less, or 23.5 mass% or less.

[0026] (9) Co ≦ 0.10 mass%: When the Co content becomes excessive, the hot workability and cold workability may decrease. Therefore, the Co content needs to be 0.10 mass% or less. The Co content is preferably 0.09 mass% or less. On the other hand, excessive reduction of the Co content may lead to an increase in cost. Therefore, it is preferable to select an optimal value for the Co content in consideration of the manufacturing cost.

[0027] (10) Al ≦ 0.10 mass%: When the Al content becomes excessive, the thermal expansion coefficient of the steel may increase. Therefore, the Al content needs to be 0.10 mass% or less. The Al content is more preferably 0.05 mass% or less. On the other hand, excessive reduction of the Al content may lead to an increase in cost. Therefore, it is preferable to select an optimal value for the Al content in consideration of the manufacturing cost.

[0028] (11) 0.01 ≦ Ti ≦ 0.30 mass%: Ti forms Ti carbide and / or Ti nitride, and suppresses the formation of Cr carbide and / or Cr nitride, thereby having the effect of improving the oxidation resistance of steel. Further, Ti forms TiO₂ during oxidation and has the effect of suppressing the volatilization of CrO₃. To obtain such an effect, the Ti content needs to be 0.01 mass% or more. The Ti content is preferably 0.05 mass% or more. On the other hand, when the Ti content becomes excessive, the hot workability and cold workability may decrease. Therefore, the Ti content needs to be 0.30 mass% or less. The Ti content is preferably 0.20 mass% or less.

[0029] (12) 0 < N ≤ 0.03 mass%: When the N content becomes excessive, Cr nitride may be formed, resulting in a decrease in the Cr concentration in the matrix phase and a possible decrease in the oxidation resistance of the steel. Therefore, the N content needs to be 0.03 mass% or less. The N content is preferably 0.02 mass% or less. On the other hand, N is also an element that inevitably mixes in, and excessive reduction leads to higher costs. Therefore, it is preferable to select an optimal value for the N content in consideration of the manufacturing cost.

[0030] (13) 0.05 ≤ La ≤ 0.30 mass%: La has the effect of improving the oxidation resistance of steel without significantly reducing the hot workability and cold workability of the steel. To obtain such an effect, the La content needs to be 0.05 mass% or more. The La content is preferably 0.07 mass% or more. On the other hand, when the La content becomes excessive, the hot workability and cold workability may decrease. Therefore, the La content needs to be 0.30 mass% or less. The La content is preferably 0.20 mass% or less.

[0031] [1.2. Sub-components] The ferritic stainless steel according to the present invention further contains one or more of the following elements in addition to the above-described elements. The types of the added elements, their component ranges, and the reasons for their limitations are as follows.

[0032] (14) 0.05 ≦ V ≦ 2.00 mass%: V forms V carbide and / or V nitride and suppresses the formation of Cr carbide and / or Cr nitride, thereby having the effect of improving the oxidation resistance of the steel. When V is contained in the steel, in order to obtain such an effect, the amount of V is preferably 0.05 mass% or more. More preferably, the amount of V is 0.10 mass% or more. On the other hand, when the amount of V is excessive, the hot workability and cold workability may decrease. Therefore, the amount of V is preferably 2.00 mass% or less. More preferably, the amount of V is 1.50 mass% or less.

[0033] (15) 0.05 ≦ Nb ≦ 2.00 mass%: Nb forms Nb carbide and / or Nb nitride and suppresses the formation of Cr carbide and / or Cr nitride, thereby having the effect of improving the oxidation resistance of the steel. When Nb is contained in the steel, in order to obtain such an effect, the amount of Nb is preferably 0.05 mass% or more. More preferably, the amount of Nb is 0.10 mass% or more. On the other hand, when the amount of Nb is excessive, the hot workability and cold workability may decrease. Therefore, the amount of Nb is preferably 2.00 mass% or less. More preferably, the amount of Nb is 1.50 mass% or less.

[0034] (16) 0.05 ≦ Ta ≦ 0.30 mass%: Ta forms Ta carbide and / or Ta nitride and suppresses the formation of Cr carbide and / or Cr nitride, thereby having the effect of improving the oxidation resistance of the steel. When Ta is contained in the steel, in order to obtain such an effect, the amount of Ta is preferably 0.05 mass% or more. More preferably, the amount of Ta is 0.07 mass% or more. On the other hand, when the amount of Ta is excessive, the hot workability and cold workability may decrease. Therefore, the amount of Ta is preferably 0.30 mass% or less. More preferably, the amount of Ta is 0.20 mass% or less.

[0035] (17) 0.0010 ≤ B ≤ 0.0100 mass%: B forms B carbide and / or B nitride and suppresses the formation of Cr carbide and / or Cr nitride, thereby having the effect of improving the oxidation resistance of the steel. When B is contained in the steel, in order to obtain such an effect, the amount of B is preferably 0.0010 mass% or more. More preferably, the amount of B is 0.0015 mass% or more. On the other hand, when the amount of B becomes excessive, the hot workability and cold workability may decrease. Therefore, the amount of B is preferably 0.0100 mass% or less. More preferably, the amount of B is 0.0050 mass% or less.

[0036] [1.3. Inevitable impurities] Inevitable impurities mean elements mixed from ores, scraps used as raw materials for steel, or the environment of the manufacturing process, etc. Specifically, in addition to C, Si, P, and S described above, other elements may be further contained as inevitable impurities.

[0037] [2. Steel sheet] The steel sheet according to the present invention is made of the ferritic stainless steel according to the present invention.

[0038] [2.1. Ferritic stainless steel] Details of the ferritic stainless steel are as described above, so the description is omitted.

[0039] [2.2. Thickness] The thickness of the steel sheet according to the present invention is not particularly limited, and an optimal thickness can be selected according to the purpose. For example, when the steel sheet according to the present invention is used for a separator for SOFC or a separator for SOEC, if the thickness is too thick, there is a risk that SOFC or SOEC will become larger in size. Therefore, the thickness is preferably 3.5 mm or less. More preferably, the thickness is 3.0 mm or less. On the one hand, if the thickness becomes too thin, the strength and / or oxidation resistance of the steel plate may decrease. Therefore, the thickness is preferably 0.1 mm or more. More preferably, the thickness is 0.5 mm or more.

[0040] [2.3. Applications] The steel plate according to the present invention can be used in any application that requires a low coefficient of thermal expansion, heat resistance, electronic conductivity, oxidation resistance, or hot workability. The steel plate according to the present invention is particularly suitable as a material for a separator for a solid oxide fuel cell (SOFC) or a separator for a solid oxide electrolysis cell (SOEC).

[0041] [3. Manufacturing method of steel plate] The steel plate according to the present invention is (a) melting and casting a raw material compounded to have a predetermined composition, (b) performing a homogenization heat treatment on the steel ingot as necessary, (c) performing hot working on the steel ingot, (d) performing primary annealing on the hot-worked body as necessary, (e) performing cold working on the hot-worked body as necessary, (f) performing secondary annealing on the hot-worked body or the cold-worked body to be manufactured thereby.

[0042] [3.1. Melting and casting process] First, a raw material compounded to have a predetermined composition is melted and cast. The melting conditions and casting conditions are not particularly limited, and optimal conditions can be selected according to the purpose.

[0043] [3.2. Homogenization heat treatment process] Next, if necessary, a homogenization heat treatment is performed on the steel ingot. The homogenization heat treatment is performed to homogenize the components of the steel ingot. When the component segregation of the steel ingot does not pose a problem, the homogenization heat treatment can be omitted. The conditions of the homogenization heat treatment are not particularly limited, and optimal conditions can be selected according to the purpose.

[0044] [3.3. Hot working process] Next, hot working is performed on the steel ingot. The "steel ingot" to be hot worked refers to a steel ingot as it is melted and cast, or a steel ingot that has undergone homogenization heat treatment. Hot working is performed to process the steel ingot into the final product shape, or to process the steel ingot into a rough shape suitable for cold working. The conditions of hot working are not particularly limited, and optimal conditions can be selected according to the purpose.

[0045] [3.4. First annealing process] Next, if necessary, first annealing is performed on the hot worked product. When further cold working is to be performed on the hot worked product, it is preferable to perform first annealing on the hot worked product. First annealing is performed to remove the strain contained in the hot worked product and improve the cold workability. Therefore, when cold working is not performed, or when the cold workability of the hot worked product is high, first annealing can be omitted. The conditions of first annealing are not particularly limited, and optimal conditions can be selected according to the purpose.

[0046] [3.5. Cold working process] Next, if necessary, cold working is performed on the hot worked product. The "hot worked product" to be cold worked refers to a hot worked product on which only hot working has been performed, or a hot worked product on which first annealing has been performed after hot working. Cold working is particularly performed when high dimensional accuracy is required. Therefore, when high dimensional accuracy is not required for the steel plate, cold working can be omitted. The conditions of cold working are not particularly limited, and optimal conditions can be selected according to the purpose.

[0047] [3.6. Second annealing process] Next, second annealing is performed on the hot worked product or the cold worked product. The "hot worked product" to be second annealed refers to a hot worked product on which only hot working has been performed. The secondary annealing is performed to remove the strain contained in the hot-worked body or cold-worked body. The conditions for the secondary annealing are not particularly limited, and the optimal conditions can be selected according to the purpose. The steel sheet thus obtained is used for various applications after additional processing is performed as necessary.

[0048] [4. Action] Ce contained in REM (mischmetal) has an effect of improving the oxidation resistance of ferritic stainless steel, but has a great effect of reducing the hot workability. On the other hand, La has an effect of improving the oxidation resistance of ferritic stainless steel and has a smaller effect of reducing the hot workability compared to Ce. Therefore, when an appropriate amount of La is added to ferritic stainless steel instead of Ce, the oxidation resistance can be improved without significantly reducing the hot workability of ferritic stainless steel.

[0049] In ferritic stainless steel, when the Al content is limited, an increase in the coefficient of thermal expansion and a decrease in electronic conductivity due to the formation of an insulating oxide film can be suppressed. In addition, Mn and Ti have an effect of forming Cr-Mn spinel-type oxides or Ti oxides when ferritic stainless steel is exposed to a high-temperature oxidation atmosphere, and suppressing the volatilization of CrO3. Furthermore, Ti, as well as V, Nb, Ta, and B, all have an effect of suppressing the formation of Cr carbides and Cr nitrides. Therefore, when one or more of the elements V, Nb, Ta, and B are further added in addition to Ti, the oxidation resistance of ferritic stainless steel is further improved.

Examples

[0050] (Examples 1 to 15, Comparative Examples 1 to 21) [1. Preparation of Samples] The raw materials formulated to have the compositions shown in Table 1 and Table 2 were melted in a vacuum induction heating furnace to obtain 15 kg ingots. Subsequently, a homogenization heat treatment was performed by heating the ingots at 1200 °C for 4 hours. Thereafter, hot forging was carried out at 1100 °C to form a plate shape with a thickness of 30 mm. Further, hot rolling was performed at 1100 °C to form a plate shape with a thickness of 10 mm.

[0051] For the obtained plate-shaped hot-formed body, annealing treatment (primary annealing) was performed by holding at 1100 °C for 2 hours and then air-cooling. Subsequently, cold rolling was carried out at room temperature to obtain a cold-formed body with a thickness of 2.5 mm. Further, vacuum annealing treatment (secondary annealing) was performed by heating the obtained cold-formed body at 800 °C for 4 hours.

[0052]

Table 1

[0053]

Table 2

[0054] [2. Test Method] [2.1. Workability] The workability was evaluated based on the degree of cracks generated in the obtained formed body during the above-mentioned hot rolling and cold rolling.

[0055] [2.2. Continuous Oxidation Test] Test pieces for the continuous oxidation test were cut out from the formed body after vacuum annealing treatment with dimensions of 2.5 mm × 15 mm × 20 mm. An oxidation test was carried out for 100 hours in the atmosphere at 800 °C according to the high-temperature continuous oxidation test method for metallic materials defined in JIS Z2281.

[0056] [2.3. Cr Evaporation Test] The test pieces for the Cr evaporation test were cut out from the formed body after vacuum annealing, with dimensions of 2.5 mm × 15 mm × 50 mm. The cut-out test pieces were placed in a quartz tube and exposed to an atmosphere of 800 °C with a dew point of 80 °C and humidified for 100 hours. After the test, the Cr oxide adhering to the inside of the quartz tube was dissolved in dilute sulfuric acid, and the amount of Cr was measured by ICP emission spectrometry to calculate the Cr evaporation amount.

[0057] [2.4. Measurement of Coefficient of Thermal Expansion] The test pieces for the coefficient of thermal expansion measurement were cut out from the formed body after vacuum annealing, with dimensions of 2.5 mm × 6 mm × 19 mm. In accordance with the method for measuring the linear expansion coefficient of metallic materials specified in JIS Z2285, the coefficient of thermal expansion from 28 °C to 800 °C was measured.

[0058] [2.5. Measurement of Contact Resistance] The test pieces for the contact resistance measurement were cut out from the formed body after vacuum annealing, with dimensions of 2.5 mm × 15 mm × 20 mm. The cut-out test pieces were oxidized in air at 800 °C for 100 hours. After oxidation, the test pieces were sandwiched and fixed between 10 mm × 10 mm Pt plates with Pt wires joined for current application and voltage measurement, and the contact resistance was measured by the four-terminal method.

[0059] [2.6. Measurement of Cr Carbonitride Area Ratio] The test pieces for the Cr carbonitride area ratio measurement were cut out from the cold-formed body after vacuum annealing, with dimensions of 2.5 mm × 10 mm × 10 mm. The surface of the test piece was polished, and after chemically etching the polished surface with Vilella's reagent, the etched surface was observed with an optical microscope. Since the carbonitride precipitates at the grain boundaries, it was estimated that all the grain boundary carbonitrides were Cr carbonitrides, and the area of each Cr carbonitride was measured. The Cr carbonitride area ratio was calculated by dividing the total area of the Cr carbonitrides observed in the range of 10 mm × 10 mm by the field area (10 mm × 10 mm).

[0060] [3. Results] The results are shown in Table 3. Figure 1 shows an optical micrograph of the ferritic stainless steel obtained in Comparative Example 1. From Table 3 and Figure 1, the following can be understood.

[0061] Regarding workability, 「◎」 indicates that a crack-free cold-formed body could be produced. 「○」 indicates that although minor cracks occurred during hot rolling, a cold-formed body could be produced without polishing treatment. 「△」 indicates that cracks occurred during hot rolling, so a cold-formed body could not be produced without polishing treatment, but a cold-formed body could be produced by polishing the hot-formed body. 「×」 indicates that it cracked during hot rolling, so it could not be cold-rolled.

[0062] Regarding oxidation resistance, 「◎」 indicates that the oxidation weight gain is 0.4 mg / cm 2 or less. 「○」 indicates that the oxidation weight gain is 0.4 mg / cm 2 more than 0.6 mg / cm 2 or less. 「△」 indicates that the oxidation weight gain is 0.6 mg / cm 2 more than 0.8 mg / cm 2 or less. 「×」 indicates that the oxidation weight gain is 0.8 mg / cm 2 more than.

[0063] Regarding Cr poisoning resistance, 「◎」 indicates that the Cr evaporation amount is 80 μg / cm 2 or less. 「○」 indicates that the Cr evaporation amount is 80 μg / cm 2 more than 90 μg / cm 2 or less. 「△」 indicates that the Cr evaporation amount is 90 μg / cm 2 more than 100 μg / cm 2 or less. 「×」 indicates that the Cr evaporation amount is 100 μg / cm 2 more than.

[0064] Regarding the coefficient of thermal expansion, 「◎」 indicates that the coefficient of thermal expansion is 12.25×10 -6 / °C or less. 「○」 indicates that the coefficient of thermal expansion is 12.25×10-6 / °C above 12.30×10 -6 represents being below / °C, "△" indicates that the coefficient of thermal expansion is above 12.30×10 -6 / °C and below 12.35×10 -6 / °C, "×" indicates that the coefficient of thermal expansion is above 12.35×10 -6 / °C.

[0065] Regarding the contact resistance, "◎" represents that the contact resistance is 40 mΩ·cm 2 or less, "○" represents that the contact resistance is above 40 mΩ·cm 2 and below 45 mΩ·cm 2 or less, "△" represents that the contact resistance is above 45 mΩ·cm 2 and below 50 mΩ·cm 2 or less, "×" represents that the contact resistance is above 50 mΩ·cm 2 or more.

[0066] Regarding the Cr carbonitride area ratio, "○" represents that the Cr carbonitride area ratio is 1% or less, "×" represents that the Cr carbonitride area ratio is above 1%.

[0067] (1) In Comparative Example 1, the oxidation resistance decreased and the Cr carbonitride area ratio increased (see Figure 1). This is presumably because, due to the excessive C content, Cr in the matrix phase was consumed in the formation of Cr carbides. (2) In Comparative Example 2, the contact resistance increased slightly. This is presumably because, due to the excessive Si content, SiO2 was formed on the outermost layer. (3) In Comparative Example 3, the Cr poisoning resistance decreased. This is presumably because, due to the low Mn content, it became difficult to form Mn-Cr-based oxides. On the other hand, in Comparative Example 4, the oxidation resistance decreased. This is presumably because of the excessive Mn content.

[0068] (4) In Comparative Example 5, the workability slightly decreased. This is considered to be because the amount of Cu was excessive. (5) In Comparative Example 6, the coefficient of thermal expansion increased. This is considered to be because Ni was excessive. (6) In Comparative Example 7, the oxidation resistance slightly decreased. This is considered to be because the amount of Cr was small. On the other hand, in Comparative Example 8, the Cr passivation resistance decreased. This is considered to be because the amount of Cr was excessive.

[0069] (7) In Comparative Example 9, the workability slightly decreased. This is considered to be because the amount of Co was excessive and the hardness of the material increased excessively. (8) In Comparative Example 10, the coefficient of thermal expansion increased. This is considered to be because the amount of Al was excessive. Also, in Comparative Example 10, the contact resistance slightly increased. This is considered to be because an Al-based oxide was formed on the outermost surface of the sample. (9) In Comparative Example 11, the oxidation resistance slightly decreased. This is considered to be because the amount of Ti was small. On the other hand, in Comparative Example 12, the workability slightly decreased. This is considered to be because the amount of Ti was excessive.

[0070] (10) In Comparative Example 13, the oxidation resistance slightly decreased. This is considered to be because the amount of La was small. On the other hand, in Comparative Example 14, the workability slightly decreased. This is considered to be because the amount of La was excessive. (11) In Comparative Example 15, the oxidation resistance slightly decreased and the Cr carbonitride area ratio increased. This is considered to be because it substantially contained none of V, Nb, Ta, and B, and thus Cr in the matrix phase was consumed for the formation of Cr carbonitride.

[0071] (12) In all of Comparative Examples 16 to 19, the workability slightly decreased. This is considered to be because the amount of V, Nb, Ta, or B was excessive. (13) In Comparative Example 20, the oxidation resistance decreased and the Cr carbonitride area ratio increased. This is considered to be because the amount of N was excessive and Cr in the matrix phase was consumed for the formation of carbonitride. (14) In Comparative Example 21, the workability slightly decreased. This is considered to be because the amount of Ce was excessive.

[0072] (15) Examples 1 to 15 all had excellent workability, oxidation resistance, and Cr poisoning resistance. Also, in Examples 1 to 15, the coefficient of thermal expansion, contact resistance, and Cr carbonitride area ratio all became small. This is considered to be because in addition to the content of each component being optimized, at least one of V, Nb, Ta, and B is contained in an appropriate amount. (16) Although the La content in Example 10 was 0.03 mass%, it showed oxidation resistance equivalent to that of Comparative Example 21 (Ce content = 0.06 mass%) and better workability than Comparative Example 21. Similarly, although the La content in Example 9 was 0.19 mass%, it showed oxidation resistance equivalent to that of Comparative Example 21 and better workability than Comparative Example 21.

[0073]

Table 3

[0074] As described above in detail regarding the embodiments of the present invention, the present invention is not limited to the above embodiments at all, and various modifications are possible without departing from the gist of the present invention.

Industrial Applicability

[0075] The ferritic stainless steel according to the present invention can be used as a separator for a solid oxide fuel cell and a separator for a solid oxide electrolysis cell.

Claims

1. 0 < C ≤ 0.03 mass%, Si ≤ 0.05 mass%, 0.30 ≤ Mn ≤ 1.00 mass%, P ≤ 0.05 mass%, S ≤ 0.05 mass%, Cu ≤ 0.10 mass%, Ni ≤ 0.20 mass%, 20.0 ≤ Cr ≤ 25.0 mass%, Co ≤ 0.10 mass%, Al ≤ 0.10 mass%, 0.01 ≤ Ti ≤ 0.30 mass%, 0 < N ≤ 0.03 mass%, and, 0.05 ≤ La ≤ 0.30 mass% comprising, the balance being Fe and inevitable impurities, 0.05 ≤ V ≤ 2.00 mass%, 0.05 ≤ Nb ≤ 2.00 mass%, 0.05 ≤ Ta ≤ 0.30 mass%, and, 0.0010 ≤ B ≤ 0.0100 mass% further comprising at least one element selected from the group consisting of a ferritic stainless steel.

2. A steel sheet made of the ferritic stainless steel according to Claim 1.

3. The steel sheet according to Claim 2, having a thickness of 3.5 mm or less.

4. The steel sheet according to Claim 2, used for a separator for a solid oxide fuel cell (SOFC) or a separator for a solid oxide electrolysis cell (SOEC).

Citation Information

Patent Citations

  • Steel for solid oxide type fuel cell separator

    JP2005320625A

  • Ferritic stainless steel and method for producing the same, and fuel cell member

    JP2018080371A

  • Ferritic stainless steel and method for producing the same, and fuel cell member

    JP2020066792A

  • Stainless steel sheet for fuel cell separators, and production method therefor

    WO2017212905A1

Cited By

  • Ferritic stainless steel and steel sheet

    EP4570941A2